Pengaruh Marmet Message Terhadap Peningkatan Produksi Asi Pada Ibu Postpartum Di Wilayah Kerja Puskesmas Tanjung Tiram Kabupaten Batu Bara Provinsi Sumatera Utara Tahun 2022 - Fitria Agustina; Srilina Br Pinem; Eka Purnamasari; Lasria Simamora; Febriana Sari; Lisa Putri Utami D (NAJ Nursing Applied Journal, 2024)
Breast milk (ASI) is a natural food that is good for babies, practical, economical and easy to digest. The reason why babies need breast milk is because breast milk has benefits, one of which is that it has many advantages, it contains important substances, it can make babies develop optimally. Breast milk also plays a role in bringing closer spiritual closeness between mother and child. The first factor that influences breastfeeding failure is the mother's lack of knowledge about exclusive breastfeeding (32%), namely mothers stop breastfeeding because breast milk production is low. Actually, this is not caused by the mother not producing enough breast milk but because of the mother's lack of knowledge. The second is caused by working mothers. The third is caused by the intensive promotion of formula milk. The purpose of this research was to determine the effect of Marmet Massage on increasing breast milk products for postpartum mothers at the Tanjung Tiram Community Health Center, Tanjung Tiram District, Batu Bara Regency, North Sumatra Province in 2022. This research uses a quasi-experimental method (Quasi Experiment) with the approach used is a comparative design of control and intervention groups (One Group Post Test Design). to determine the effect of Marmet Massage on increasing breast milk products in postpartum mothers. In this study, the samples were all non-working mothers who had babies aged 0-6 months as many as 30 people with 15 people in each group who received marmet massage during the 1-4th day in a row followed by breast milk measurement for 30 minutes and The guinea pig technique was not carried out followed by breast milk measurement. Conclusion, Based on the results of research and data analysis that has been carried out regarding the Influence of the Marmet Technique on the Fluency of Mother's Milk in the Working Area of ​​the Tanjung Tiram Health Center, Tanjung Tiram District, Batu Bara Regency, North Sumatra Province in 2022, it can be concluded that: The Marmet Technique has a significant influence on the Fluency Breast milk. This is indicated by the results of the Wilcoxon test sig-p value (0.007) < 0.05